TECHNICAL AND LEGISLATIVE FACTORS EFFECTS ON THE EFFICIENCY AND EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS AND SUPPLY CHAIN MANAGEMENT - Razzaq Alwan AL-yasar, Abdulwahab; Mohammed Hussein, Jasim; Idan Barrak, Jasim (International Journal of Supply Chain Management, 2019)
An accounting information system can be considered as an element of the company that provides users with processing financial events for decision making. A set of processes and techniques that organizes information and uses it in decision making. The purpose of the present study was to investigate the technical and legislative factors on the efficiency and effectiveness of accounting information systems and supply chain management. After reviewing the seven key factors of efficiency and effectiveness, the results showed that the factors of separation of activities from accounting, disclosure rate, and cost effectiveness, internal and external audit have the most impact on the efficiency and efficiency of accounting information systems.